Kebiasaan makan teripang pasir (Holothuria scabra) dan teripang getah (Holothuria vagabunda) di Perairan Karas, Kota Batam, Indonesia - Dini, Deskarosa Rahma; Susiana, Susiana; Suryanti, Ani (Sekolah Tinggi Ilmu Pertanian Wuna, 2020)
The aim of this study was to find out the types of food eaten by sea cucumber sand (H. scabra) and sea cucumber (H. vagabunda), to know the habits of eating sea cucumber (H. scabra) and sea cucumber (H. vagabunda) in Karas waters, Galang District, Batam City. Determination of sampling points using results of the study found 3 types of sea cucumber food namely percentage, Bacillariophyceae 49,82%, Sarcodina 2,23%, Crustacea 24,33%, and 5 types of food Sea Cucumber Seafish with percentage, Bacillariophyceae 50,75%, Sarcodina 3,91%, Crustacea 4,83%, Copepoda 0,52%, and Seagrass Fiber 0,30%.